2021
DOI: 10.1108/sef-11-2020-0449
|View full text |Cite
|
Sign up to set email alerts
|

Volatility transmission across international markets amid COVID 19 pandemic

Abstract: Purpose This paper aims to investigate the volatility transmission across stocks, gold and crude oil markets before and during the novel coronavirus (COVID-19) crisis. Design/methodology/approach A multivariate vector autoregression (VAR)-Baba, Engle, Kraft and Kroner generalized autoregressive conditional heteroskedasticity model (BEKK-GARCH) is used to assess volatility transmission across the examined markets. The sample is divided as follows. The first period ranging from 02/01/2019 to 10/03/2020 defines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Furthermore, this study employed the volatility spillover procedure of Diebold and Yilmaz's (2012) to approximate the level of risk of exportation associated with China to the G7 nations. As the advanced event study methodology involves analyzing the impact of specific events on the stock market by examining abnormal returns and the volatility spillover procedure assesses how fluctuations in one market can affect volatility in another, these methodologies are relevant to our study due to their potential to provide a framework for understanding market reactions to significant events like the COVID-19 pandemic (Ajmi et al, 2021). The findings revealed that all the stock markets of G7 countries are suffering subject to uncertainty emanating from the COVID -19 epidemic.…”
Section: Literature Review 21 Global Impact Of Covid-19 On Stock Marketsmentioning
confidence: 99%
“…Furthermore, this study employed the volatility spillover procedure of Diebold and Yilmaz's (2012) to approximate the level of risk of exportation associated with China to the G7 nations. As the advanced event study methodology involves analyzing the impact of specific events on the stock market by examining abnormal returns and the volatility spillover procedure assesses how fluctuations in one market can affect volatility in another, these methodologies are relevant to our study due to their potential to provide a framework for understanding market reactions to significant events like the COVID-19 pandemic (Ajmi et al, 2021). The findings revealed that all the stock markets of G7 countries are suffering subject to uncertainty emanating from the COVID -19 epidemic.…”
Section: Literature Review 21 Global Impact Of Covid-19 On Stock Marketsmentioning
confidence: 99%
“…The index created by Diebold and Yilmaz (2008) has an important place in the literature in terms of investigating the dynamics of return spillover and volatility spillover. Ajmi et al (2021) and, Ghorbel and Jeribi (2021), while examining volatility transmission and spillovers, discussed Bitcoin's hedging tool properties and whether it is a safe haven for various asset classes such as gold, stock market and energy commodities. In addition, Dyhrberg (2016) investigated whether Bitcoin is a hedging tool for FTSE and different parities.…”
Section: Literaturementioning
confidence: 99%
“…In their article, Ajmi et al (2021) looked at how volatility was transferred across equities, gold, and crude oil before and during the COVID-19 crisis. The sample, which started from the date 02.01.2019 and ended at the date 05.10.2020, was divided into two periods, the pre-COVID period and the COVID crisis period.…”
Section: Literaturementioning
confidence: 99%
“…This hypothesis is motivated by the ability of gold to minimize the risk of stocks during the pandemic, which has been well documented (Padhan & Prabheesh, 2021). One limitation of the literature is that mostly non-MSGARCH models are used to measure the hedge effectiveness of gold against the risk of stocks during the pandemic (Ajmi et al, 2021;Corbet et al, 2020;Fakhfekh et al, 2021;Sikiru & Salisu, 2021).…”
Section: Introductionmentioning
confidence: 99%